Professional ethics of accountants based on the Qur’an: Is it still relevant? - Trihatmoko, Huda; Sari, Tyasha Ayu Melynda; Mubaraq, Muhammad Raihan (Universitas Hayam Wuruk Perbanas, 2024)
This study aims to contribute to the ethics of accountants in accordance with the values in the Qur’an. The accounting profession faces many ethical challenges, especially in terms of behavior. Ethical issues in business and professions, including accounting, continue to occur from time to time, both in Indonesia and in other countries. Indonesia, which is predominantly Muslim, is also not free from ethical violations in the accounting profession. This phenomenon raises discussions about how an accountant should behave. The research method used in this study is a literature review which is carried out by collecting, evaluating, and synthesizing various literatures relevant to the topic being studied. The analysis is carried out using an Islamic ethical theory approach based on the Qur’an and Hadith, where the findings from the literature are compared and evaluated based on Islamic ethical principles. The Indonesian Institute of Accountants (IAI) has formulated a code of ethics for the accounting profession which contains various rules regarding the behavior of accountants. All accountants must comply with the code of ethics. However, because the code of ethics does not have strict sanctions when a violation occurs, its application depends more on the personal awareness of the accountant. When someone who is pursuing a profession only relies on self-awareness, he must pay attention to his conscience. This study attempts to provide an offer on how the Qur’an uses conscience to regulate ethics that can be used in the Indonesian accounting profession.